Protective Effect of PPARγ Agonists on Cerebellar Tissues Oxidative Damage in Hypothyroid Rats - Yousef Baghcheghi; Farimah Beheshti; Hossein Salmani; Mohammad Soukhtanloo; Mahmoud Hosseini (Neurology Research International)
The aim of the current study was to investigate the effects of peroxisome proliferator-activated receptor gamma (PPARγ) agonists on cerebellar tissues oxidative damage in hypothyroid rats. The animals included seven groups: group I (control), the animals received drinking water; group II, the animals received 0.05% propylthiouracil (PTU) in drinking water; besides PTU, the animals in groups III, IV, V, VI, and VII, were injected with 20 mg/kg vitamin E (Vit E), 10 or 20 mg/kg pioglitazone, and 2 or 4 mg/kg rosiglitazone, respectively. The animals were deeply anesthetized and the cerebellar tissues were removed for biochemical measurements. PTU administration reduced thiol content, superoxide dismutase (SOD), and catalase (CAT) activities in the cerebellar tissues while increasing malondialdehyde (MDA) and nitric oxide (NO) metabolites. Vit E, pioglitazone, and rosiglitazone increased thiol, SOD, and CAT in the cerebellar tissues while reducing MDA and NO metabolites. The results of present study showed that, similar to Vit E, both rosiglitazone and pioglitazone as PPARγ agonists exerted protective effects against cerebellar tissues oxidative damage in hypothyroid rats.